2016
DOI: 10.22161/ijaers/3.10.24
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Livestock Feed Resource and Effect of Supplementing Sweet Potato Vine Hay on Growth Performance and Feed Intake of Grazing Local Goats in Aleta Chuko District, Sidama Zone SNNPRS, Ethiopia

Abstract: Through a diagnostic survey and feeding trials (Aleta Chuko Woreda, SNNPRS), availability of common feed resources and effect of sweet potato vine hay (SPVH) and concentrate (50%wheat bran +50% noug cake) supplementation to local bucks on growth performance were assessed at farmers' management levels. Out of 150 households (HHs) interviewed it was found that natural pasture, crop residues, fodder tree and industrial by products are main feed resources; livestock are mainly kept for milk production and income b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
7
1
0
Order By: Relevance
“…Crop residues contributed the largest portion of feed DM during the dry season which agrees with earlier report [9]. The DM contribution reported for crop residues in the current study agrees with earlier reports [48,49]. On the other hand, the DM contribution of crop residues in the current study was greater [1,6,14,32,50,51], but lower than earlier reports [11,31,52].…”
Section: Contribution Of Feed Resourcessupporting
confidence: 91%
See 3 more Smart Citations
“…Crop residues contributed the largest portion of feed DM during the dry season which agrees with earlier report [9]. The DM contribution reported for crop residues in the current study agrees with earlier reports [48,49]. On the other hand, the DM contribution of crop residues in the current study was greater [1,6,14,32,50,51], but lower than earlier reports [11,31,52].…”
Section: Contribution Of Feed Resourcessupporting
confidence: 91%
“…This might have been due to differences in variety of cultivated forages. The DM contribution of purchased feeds in the present study was comparable with the previous results reported [6,41,49], but it was higher [1,14], and lower than those earlier reported [44,53]. These differences might be due to differences in DM content of purchased feeds.…”
Section: Contribution Of Feed Resourcessupporting
confidence: 88%
See 2 more Smart Citations
“…In these two regions sweetpotato roots and vines are also used as livestock feed. The feed quality of the vines is regarded as high owing to its good palatability, digestibility and high crude protein concentration (Ayele and Peacock, 2003;Negesse et al, 2016).…”
Section: Introductionmentioning
confidence: 99%